Exogenous Nicotinamide Adenine Dinucleotide Attenuates Postresuscitation Myocardial and Neurologic Dysfunction in a Rat Model of Cardiac Arrest. Issue 2 (22nd September 2021) - Su, Chenglei; Xiao, Yan; Zhang, Guozhen; Liang, Lian; Li, Hui; Cheng, Cheng; Jin, Tao; Bradley, Jennifer; Peberdy, Mary A.; Ornato, Joseph P.; Mangino, Martin J.; Tang, Wanchun
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To investigate the therapeutic potential and underlying mechanisms of exogenous nicotinamide adenine dinucleotide + on postresuscitation myocardial and neurologic dysfunction in a rat model of cardiac arrest. DESIGN: Thirty-eight rats were randomized into three groups: 1) Sham, 2) Control, and 3) NAD. Except for the sham group, untreated ventricular fibrillation for 6 minutes followed by cardiopulmonary resuscitation was performed in the control and NAD groups. Nicotinamide adenine dinucleotide + (20 mg/kg) was IV administered at the onset of return of spontaneous circulation. SETTING: University-affiliated research laboratory. SUBJECTS: Sprague-Dawley rats. INTERVENTIONS: Nicotinamide adenine dinucleotide + . MEASUREMENTS AND MAIN RESULTS: Hemodynamic and myocardial function were measured at baseline and within 4 hours following return of spontaneous circulation. Survival analysis and Neurologic Deficit Score were performed up to 72 hours after return of spontaneous circulation. Adenosine triphosphate (adenosine triphosphate) level was measured in both brain and heart tissue. Mitochondrial respiratory chain function, acetylation level, and expression of Sirtuin3 and NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, 9 (NDUFA9) in isolated mitochondrial protein from both brain and heart tissue were evaluated at 4 hours following return of spontaneous circulation. The results demonstrated that nicotinamide adenine dinucleotide + treatment improved mean arterial pressure (at 1 hr following return of spontaneous circulation, 94.69 ± 4.25 mm Hg vs 89.57 ± 7.71 mm Hg; p < 0.05), ejection fraction (at 1 hr following return of spontaneous circulation, 62.67% ± 6.71% vs 52.96% ± 9.37%; p < 0.05), Neurologic Deficit Score (at 24 hr following return of spontaneous circulation, 449.50 ± 82.58 vs 339.50 ± 90.66; p < 0.05), and survival rate compared with that of the control group. The adenosine triphosphate level and complex I respiratory were significantly restored in the NAD group compared with those of the control group. In addition, nicotinamide adenine dinucleotide + treatment activated the Sirtuin3 pathway, down-regulating acetylated-NDUFA9 in the isolated mitochondria protein. CONCLUSIONS: Exogenous nicotinamide adenine dinucleotide + treatment attenuated postresuscitation myocardial and neurologic dysfunction. The responsible mechanisms may involve the preservation of mitochondrial complex I respiratory capacity and adenosine triphosphate production, which involves the Sirtuin3-NDUFA9 deacetylation.